Influence of Lemek Sari Organic Fertilizer and NPK Tawon on the Growth and Yield of Chili - I Kadek Sudiadnyana; Yohanes Parlindungan Situmeang; Ida Bagus Komang Mahardika (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2026)
This study investigated the effects of Lemek Sari organic fertilizer and NPK Tawon inorganic fertilizer on the growth and yield of chili (Capsicum annuum L.). A randomized block design with a factorial arrangement was employed, incorporating five Lemek Sari doses (0, 10, 20, 30, 40 t ha?¹) and four NPK Tawon doses (0, 200, 400, 600 kg ha?¹). NPK Tawon fertilizer exerted highly significant effects (P < 0.01) on all measured growth and yield parameters. The optimum dose of 600 kg ha?¹ produced the highest fruit weight (202.37 g), representing a 2073.68% increase over the unfertilized control. Lemek Sari organic fertilizer applied independently had a significant effect solely on stem diameter (P < 0.05), whereas the 40 t ha?¹ dose elevated fruit weight by 90.07% relative to the control. A highly significant synergistic interaction (P < 0.01) was observed for the number of harvested fruits, with the combination of 40 t ha?¹ Lemek Sari and 600 kg ha?¹ NPK Tawon yielding the highest fruit number (34.67 fruits per plant), compared to zero fruits in the unfertilized control. Correlation analysis revealed near-perfect positive relationships (r > 0.90) among vegetative and generative parameters under NPK Tawon treatment, confirming that macronutrient supply acted as the primary limiting factor for yield formation. These findings demonstrate that soil improvement by high-dose Lemek Sari organic fertilizer maximizes the efficiency of NPK Tawon, providing a scientifically grounded strategy for sustainable intensification of chili production.